2010
DOI: 10.1037/a0019767
|View full text |Cite
|
Sign up to set email alerts
|

The rational-choice theory of neurosis: Unawareness and an integrative therapeutic approach.

Abstract: In agreement with Freud (1915aFreud ( , 1915b, patients' unawareness regarding the underlying causes of their behavior seems to be the key to understanding the development and treatment of neurotic disorders. However, Freud's concepts of the unconscious and repression have encountered serious problems that do not allow for their maintenance (see review by Rofe ´, 2008). An additional issue concerns the fact that none of the available theories can integrate the therapeutic effects of various interventions under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 345 publications
(450 reference statements)
0
13
0
4
Order By: Relevance
“…As noted previously, there is a unanimous agreement among researchers that a diagnostic approach guided by a theory, as suggested by RCTN, which already proved its ability to integrate research and clinical data pertaining to neurosis and psychosis (Rofé, 2000(Rofé, , 2010(Rofé, , 2016Rofé & Rofé, 2013), is preferable over atheoretical, arbitrary diagnostic approaches as proposed by the DSM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted previously, there is a unanimous agreement among researchers that a diagnostic approach guided by a theory, as suggested by RCTN, which already proved its ability to integrate research and clinical data pertaining to neurosis and psychosis (Rofé, 2000(Rofé, , 2010(Rofé, , 2016Rofé & Rofé, 2013), is preferable over atheoretical, arbitrary diagnostic approaches as proposed by the DSM.…”
Section: Discussionmentioning
confidence: 99%
“…Freud assumed the existence of an autonomous, unconscious entity that supposedly had the omnipotent ability to control the patient's daily functions. In contrast, RCTN claims that patients become unaware of their deliberate adaption and maintenance of their mad behaviors, both in neuroses and psychoses, as a result of a complex self-deceptive process (Rofé, 2000(Rofé, , 2010(Rofé, , 2016Rofé & Rofé, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the discussion section, it will be indicated that despite serious weaknesses, conditioning theory appears to be the strongest explanation of simple phobia. The Rational-Choice Theory of Neurosis (Rofé, 2010;Y. Rofé & Rofé, 2013), was suggested as the best explanation of bizarre phobia (e.g., chocolate phobia or panic disorder).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, while biological factors certainly increase the vulnerability to developing fear and phobia, findings have not yet confirmed that these behaviors are controlled by biological mechanisms. A new theory, the Rational-Choice Theory of Neurosis (Rofé, 2010;Y. Rofé & Rofé, 2013), which preserves the psychoanalytic claim that bizarre phobias need to be explained within a theory that accounts for neuroses by one set of theoretical concepts, was used to resolve the theoretical confusion in this field.…”
mentioning
confidence: 99%